The Impact of Community Empowerment Programs on Oral Health Education for Knowledge Improvement in the Elderly - Nurina Febriyanti Ayuningtyas, - (Light House Polyclinic, 2022)
Objective This study aims to assess whether community empowerment as a health promotion program can improve the knowledge of the elderly and develop selfawareness about their oral health. The elderly population has increased in number and needs special attention, especially regarding the improvement of hygiene and health. Community empowerment is a type of health promotion program that can take the form of counseling and providing knowledge about oral health to the elderly. Materials and Methods Participants are elderly aged 60 years or older. Counseling was done by oral medicine specialists and residents to provide knowledge about oral health problems. Assessment of knowledge improvement was done using pretest and posttest in a written questionnaire. Statistical Analysis The Shapiro–Wilk test followed by the Wilcoxon test was used to compare the difference before and after counseling. Results From a total of 38 elderly included in this study, 29 (76.32%) showed an improved score in posttest compared with pretest. Statistical analysis showed a significant difference between pretest and posttest scores of study participants (p < 0.005). Conclusion Counseling in empowerment programs can help the elderly improve their knowledge about oral health, so that improvements can be expected to be followed by the development of self-awareness in the future.